Embodied Motherhood: An Exploration of Body Image in Pregnant and Parenting Youth. (1st June 2016) - Harrison, M; Obeid, N; Rohde, K; McLean, N; Haslett, K; Simpson, C; Barriault, D; Clarkin, C
Abstract: BACKGROUND: Pregnancy is associated with changes in body shape that influence body image satisfaction. Body dissatisfaction during pregnancy is a concern because of the potential association with negative behaviours, such as unhealthy dieting, which have been linked to poor pregnancy and neonatal outcomes. This is of particular concern for pregnant youth as they are already at increased risk for medical complications. Body image dissatisfaction in pregnancy is also an important determinant of depressive symptoms in pregnancy and postpartum. Given that pregnant and parenting youth (PPY) have poorer mental health outcomes, including a high rate of both antenatal and postpartum depression, examining the relationship between body image and depression during pregnancy is particularly important. OBJECTIVES: The objectives of this study were to 1) examine psychological profiles of PPY regarding body image and related issues, 2) explore differences between younger and older PPY, and 3) compare psychological profiles of those who are pregnant versus not pregnant. DESIGN/METHODS: Data was collected from 75 PPY from 2 urban social service agencies via electronic questionnaires. Demographic data and scores from several validated self-report measures related to self-esteem, body esteem, eating disorder behaviours and depression were collected. Research ethics board approval was obtained prior to the onset of the study. RESULTS: Youth participants had a mean age of 19.6 years (SD=2.68); 29.3% (n=22) were pregnant at the time of the survey and 82.7 % (n=62) had at least 1 child. Youth reported a past history of depression (76.9%), anxiety (70.5%), drug/alcohol abuse (46.2%), and eating disorder (28.2%). Descriptive analyses revealed that PPY reported depression scores that were in the borderline clinical range (Edinburgh postnatal depression scale: mean 11.57, SD 6.26), whereas they scored within the relative normal range for all other psychological measures. There were no significant differences in any of the survey scores when comparing younger to (n=39, mean age 17.5 yrs) older participants (n=36, mean age 22 yrs); although when comparing pregnant (n=22) participants and non-pregnant (n=53) participants significant differences were found among scores of body esteem (t=-2.173, p=0.034) and eating disorder behaviours (t=2.713, p=0.008). CONCLUSION: This study adds to the very limited research regarding adolescents' experience with body image during motherhood and the postpartum years, and can inform future program development for pregnant teens and young mothers struggling with poor body image. Future research is needed to continue exploring how adolescent body image during pregnancy and postpartum may differ and how this affects maternal and child outcomes.